2018
DOI: 10.1097/aln.0000000000002324
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of the Surgeon–Anesthesiologist Relationship for Patient Safety

Abstract: Teamwork is now recognized as important for safe, high-quality perioperative care. The relationship in each surgeon–anesthesiologist dyad is perhaps the most critical element of overall team performance. A well-functioning relationship is conducive to safe, effective care. A dysfunctional relationship can promote unsafe conditions and contribute to an adverse outcome. Yet, there is little research about this relationship, about what works well or not well, what can be done to optimize it. This article explores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 13 publications
0
42
0
Order By: Relevance
“…Surgeons might feel that anesthesiologists are inattentive or distracted during an operation. 18 Anesthesiologists might find surgeons so absorbed with the technical aspects of surgery that they fail to acknowledge their patients' health conditions and how these comorbidities could influence perioperative care. 18…”
Section: Literature On Breaksmentioning
confidence: 99%
“…Surgeons might feel that anesthesiologists are inattentive or distracted during an operation. 18 Anesthesiologists might find surgeons so absorbed with the technical aspects of surgery that they fail to acknowledge their patients' health conditions and how these comorbidities could influence perioperative care. 18…”
Section: Literature On Breaksmentioning
confidence: 99%
“…As the case highlights, the dynamics between these 2 physicians-who might share, yield, or compete for leadership in operating room settings-can ultimately facilitate or impede success. 3 This article explores how joint decision making is best achieved despite disagreements and how collegial, collaborative relationships can be preserved to prioritize patients' safety during risk assessment and goal setting.…”
Section: Commentarymentioning
confidence: 99%
“…If an anesthesiologist-surgeon relationship functions well, each clinician can help the other, which serves the interest of the patient. 3 If this relationship does not function well, working environments can be unpleasant and unproductive. In the above case, the relationship between the anesthesiologist and surgeon is not a long-standing one, and significant generational and hierarchical differences exist.…”
Section: Communicating For Collegiality and Patient Safetymentioning
confidence: 99%
“…17 18 Though all team members play an important role, the relationship between the surgeon-anaesthesiologist dyad, who 'sometimes share, yield or compete for leadership', most critically influences overall OR team performance. 19 Research has identified tension between anaesthesiologists and surgeons as potentially arising from misperceptions of each other and discrepant views on which their quality of collaboration and communication was built. [19][20][21][22][23][24] Though power struggles in the OR have often been attributed to differences in professional training or values, 15 research increasingly suggests that sex (ie, biological, anatomical and physiological characteristics) and gender (ie, identity,…”
Section: Introductionmentioning
confidence: 99%